PERBEDAAN PENGETAHUAN KADER SEBELUM DAN SESUDAH DILAKUKAN TELEEDUKASI MENCUCI TANGAN DI TENGAH WABAH COVID-19 DI KELURAHAN BURANGRANG, BANDUNG - Fachreza Aryo Damara (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Background: Health prevention and promotion are both important in making better public health. In order to actualize both aspects, Posyandu cadre play major role. Cadre have bigger chance and impact to educate the people who are living around them. However, doing a direct education has become more difficult since physical contacts were minimalized during this COVID-19 outbreak. Therefore, an effective tele-education is needed as an effort to prevent COVID-19 transmission. The study aims to evaluate the effect of tele-education through Youtube and Whatsapp to enhance people's understanding on COVID-19 transmission prevention Method: The study was a cross-sectional study with observational descriptive-analytical methods and quantitatively approach. Subject of the study was Posyandu cadre in Burangrang Village, Lengkong District, Bandung with the subject total was 19. Results: After given a tele-education, there was an increase in total score means between pretest and posttest with p=0.000 (p<0.001). Moreover, there were increases in both social media’s impression and engagement on educational video which was uploaded on Youtube. Discussion: In doing tele education to Posyandu cadre, video as a media to deliver the content was more preferred. Sharing the knowledge through video along with evaluating participants' understanding of the given topics could enhance cadre knowledge about handwashing as a prevention in the middle of COVID-19 outbreak. Conclusion: Tele education using video could enhance cadre’s understanding about handwashing. The media that has been used was able to deliver the content based on impression and engagement evaluations.